# Did I simplify this right?

## Homework Statement

y - 1 / 3 = 1 / 3 (x - ln(1/3))

## The Attempt at a Solution

y - 1 / 3 = 1 / 3 (x - ln(1/3))

0 = 1 /3 x - 1/3 ln(1 / 3) + 1 / 3 - y

0 = x - ln(1 / 3) + 1 - 3y

I don't see any problem with it.

Text book says it's wrong. >_<

The answer is = x - 3y + (1 + ln3) = 0

## Answers and Replies

You have pretty much the same thing, except that they have used

$$\text{ln}( 1/x ) = \text{ln}( x^{-1} ) = -\text{ln}(x)$$

to convert $\text{ln}(1/3)$ to $-\text{ln}(3)$.

SammyS
Staff Emeritus
Homework Helper
Gold Member

## Homework Statement

y - 1 / 3 = 1 / 3 (x - ln(1/3))

## The Attempt at a Solution

y - 1 / 3 = 1 / 3 (x - ln(1/3))

0 = 1 /3 x - 1/3 ln(1 / 3) + 1 / 3 - y

0 = x - ln(1 / 3) + 1 - 3y

I don't see any problem with it.

Text book says it's wrong. >_<

The answer is = x - 3y + (1 + ln3) = 0
Your result and the book answer are equivalent.

ln(1/3) = ln(3-1) = (-1) ln(3)

You have pretty much the same thing, except that they have used

$$\text{ln}( 1/x ) = \text{ln}( x^{-1} ) = -\text{ln}(x)$$

to convert $\text{ln}(1/3)$ to $-\text{ln}(3)$.
Thank you very much. :]

Your result and the book answer are equivalent.

ln(1/3) = ln(3-1) = (-1) ln(3)

Thank you very much. :]